Enhancing Development Through Teleoccupational Therapy in Children With Cortical Visual Impairment: A Quasiexperimental Study. - Heybet, Safa; Cevher Eylen, Seval; Hilton, Claudia (Occupational Therapy International, 2026)
Purpose: This study was aimed at investigating the effectiveness of a teleoccupational therapy intervention program in improving developmental and play skills in children diagnosed with cortical visual impairment (CVI). The intervention was structured based on the person–environment–occupation (PEO) model. Materials and Methods: A quasiexperimental, pretest–posttest study design was employed with eight children aged 4–6 diagnosed with CVI. The intervention consisted of 12 weekly online occupational therapy sessions, focused on visual perception, motor skills, and environmental adaptation strategies. Outcome measures included the Ankara Developmental Screening Inventory (ADSI) and the Revised Knox Preschool Play Scale (RKPPS). Data were analyzed using the Wilcoxon signed‐rank test. Results: Significant improvements were observed in motor accuracy, visual attention, and sensory processing after the intervention (p < 0.05). Parental reports indicated increased engagement in purposeful play and daily routines. No adverse effects were reported. Conclusion: The findings support the feasibility and effectiveness of teleoccupational therapy based on the PEO model in enhancing developmental and play skills in children with CVI. The approach offers a viable alternative when in‐person services are limited.